Anatomia comparada do lenho de Tabebuia aurea (Bignoniaceae) e Tocoyena formosa (Rubiaceae) que ocorrem no cerrado e na caatinga - Dória, Larissa Chacon [UNESP] (2014)
The cerrado and caatinga are Brazilian phytogeographic domains which differ mainly in relation to latitude, temperature, water availability and soil conditions. Thus, in order to verify anatomical strategies, our goal was compare the wood anatomy of Tabebuia aurea (Bignoniaceae) and Tocoyena formosa (Rubiaceae) occurring in cerrado and caatinga to test whether anatomical differences occur and whether individuals belonging to caatinga exhibit a greater degree of xeromorphism. In cerrado we collected in Pratânia municipality, São Paulo state (22 º 48'35 '' S and 48 º 39'57 '' W) and in caatinga in São João do Cariri municipality, Paraíba state (7 º 23'27 '' S and 36 ° 32'2 '' W) and Serra Branca municipality, Paraíba state (7 º 29'14 '' S and 36 º 39'51 '' W). We collected wood samples from five individuals of each species in each area. We observed in the field a striking difference in bark thickness of the T. aurea belonging two different environments, so we collected bark samples from this species and we compared the bark percentage in these samples. The results of MANOVA showed that individuals of the two species differed by anatomical characters in different environments, showing a meaningful p value. Related to T. aurea individuals from cerrado invest in protective tissue observed by larger thickness of the bark and in radial conduction by greater height and width of rays. In caatinga, individuals invest in conductivity and water security observed by vessels of narrow diameter. Regarding to T. formosa the xeromorphic characters, like index group, vessel frequency and vulnerability and mesomorphy index were more pronounced in individuals from cerrado. We hypothesized that the soil conditions of the cerrado that shows high levels of aluminum should be more effective in this response as temperature and precipitation